Corporate Environmental Crime and the Crisis of Environmental Criminal Law Enforcement - Sutikno, Edi; Rizki, Muh; Sudirwan, Sudirwan; Jera, Almi (Muhammadiyah Law Review Journal, 2026)
Environmental crimes committed by corporations are one of the main causes of massive, systemic, and sustainable environmental damage. Although various environmental legal instruments are available, the practice of enforcing environmental criminal law shows a weak and ineffective tendency in proportionally prosecuting corporate perpetrators. This article aims to analyze the crisis in environmental criminal law enforcement in dealing with corporate environmental crimes, as well as to identify the structural and normative factors that cause legal impunity. This study uses a normative-critical legal approach supported by a green criminology perspective to examine legislation, court decisions, and environmental law enforcement policies. The results of the study show that the dominance of an administrative approach, the limitations of the application of corporate criminal liability, and the low ecological orientation of criminal policy are the main factors contributing to the weak deterrent effect of environmental criminal law. This article argues that without reconstructing environmental criminal law policies that treat corporate environmental crimes as serious crimes against the public interest and ecosystem sustainability, environmental damage will continue to recur. The findings of this study are expected to contribute theoretically and practically to strengthening the enforcement of environmental criminal law in the context of sustainable environmental protection.